2015
DOI: 10.1134/s1023193515050171
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite network polymer gel-electrolytes: TiO2- and Li2TiO3-nanoparticle effects on their structure and properties

Abstract: The effects of TiO 2 (~60 nm) and Li 2 TiO 3 (~20 nm) nanoparticles on the conductivity, struc ture, and mechanical strength of (polyether diacrylate-LiClO 4 -ethylene carbonate) based polymer gel electrolytes are studied. When the gel electrolytes are synthesized with the TiO 2 and Li 2 TiO 3 nanoparticles ultrasonic pretreatment, both polyether diacrylate and ethylene carbonate are partially decomposed in the solution; this is evidenced by the appearance of -CH 3 group signal at 1.2 ppm in 1 H NMR spectra, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The main direction of investigations is lithium cation surroundings, local and macroscopic mobilities of Li + and F − -containing fragments, and electrolyte composition-ion transport correlations. Modern and complicated NMR techniques are employed, especially solid-state high resolution magic angle spinning (MAS) NMR, pulsed-field gradient NMR, and NMR spin relaxation [13,29,[32][33][34]37,39,40,42,47,[49][50][51][52][53][54][56][57][58][59][60][61]65,72,73,76,77,80,92,.…”
Section: Nmr Study Of Polymer Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main direction of investigations is lithium cation surroundings, local and macroscopic mobilities of Li + and F − -containing fragments, and electrolyte composition-ion transport correlations. Modern and complicated NMR techniques are employed, especially solid-state high resolution magic angle spinning (MAS) NMR, pulsed-field gradient NMR, and NMR spin relaxation [13,29,[32][33][34]37,39,40,42,47,[49][50][51][52][53][54][56][57][58][59][60][61]65,72,73,76,77,80,92,.…”
Section: Nmr Study Of Polymer Electrolytesmentioning
confidence: 99%
“…NMR studies in nanocomposite polymer electrolytes were considered in [49,65,72,73,77,92,101,[104][105][106].…”
Section: Nmr In Nanocomposite Polymer Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the incorporation of TiO 2 NPs to the GPE improved its electrochemical stability and ionic conductivity in LIBs. Yamolenko et al [ 89 ] extended this study on the effect of NPs to a polyester-diacrylate (PEDAC)-based network polymer electrolyte. The mechanical strength of the GPE was enhanced after improving the distribution of the NPs in the polymer electrolyte by ultrasonic treatment compared to simple mechanical stirring.…”
Section: Details Of the Inorganic Fillers Applied In Gpesmentioning
confidence: 99%
“…Reticular gel electrolyte samples with different contents of BMIBF 4 and PC and EC solvents were prepared by radical polymerization [14]. Polymer ization of PEG DAc was performed at 80°С for 3 h in the presence of the benzoyl peroxide radical initiator (1 wt %) in a hermetically sealed glass reactor.…”
Section: Synthesis Of Polymer Gel Electrolytesmentioning
confidence: 99%